Effectiveness of A Simulated Thermodynamics Lab in A Grade Eight Lyceum Class - Sharifov, G; MacIsaac, D (Jurnal Pendidikan Fisika Indonesia, 2021)
We examine the use of PhET (University of Colorado Physics Education Technology) simulation labs in developing conceptual understanding of introductory thermodynamics by eighth grade students. Pedagogical experiments were conducted at the Baku European Lyceum, a gifted / magnet school in the capital of Azerbaijan. Results showed that virtual laboratories can play a crucial role in lyceum students' thinking and creative abilities and their acquisition of more in-depth knowledge and skills on thermodynamics.Â  We also found that simulations have many appropriate advantages in learning and teaching lyceum thermodynamics, and list seven such.